Diagnostics of inflammatory tuboovarian complexes - L. I. Kokh; N. G. Balakshina (Бюллетень сибирской медицины)
Objective differential diagnosis inflammatory tuboovarian complex in patients hospitalized following emergency visit were investigated. We examined and operated 123 patients with acute abdomen symptom hospitalized at the inpatient gynecology department Regional Clinical Hospital following emergency visit.